Successful treatment with nab-paclitaxel and gemcitabine after FOLFIRINOX failure in a patient with metastasized pancreatic adenocarcinoma - Berger, Anne Katrin; Weber, Tim; Jäger, Dirk; Springfeld, Christoph (Onkologie, 2013)
Background: Advanced pancreatic adenocarcinoma still remains associated with a desperate prognosis. Nevertheless, treatment options for patients with metastasized disease have improved considerably over the last few years. Recently, cytotoxic combination therapies such as the FOLFIRINOX regimen and combined nab-paclitaxel/gemcitabine have shown improved overall survival compared to gemcitabine alone. There is still no standard of care in second-line therapy for patients with disease progression. Case Report: We report the case of a 47-year-old patient who dramatically responded to second-line treatment with nab-paclitaxel and gemcitabine after primary progression to the FOLFIRINOX protocol. Conclusion: Second-line treatment after FOLFIRINOX is feasible for patients with good performance status. Our case report supports preclinical findings that suggest that pancreatic cancer is a heterogeneous disease. Further studies that characterize possible subgroups and identify predictive molecular markers to guide therapy are warranted.
Gesehen am 23.11.2020